2020
DOI: 10.1101/2020.04.17.20069211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Web-based, Mobile Responsive Application to Screen Healthcare Workers for COVID Symptoms: Descriptive Study

Abstract: BackgroundThe COVID-19 pandemic has impacted over 1 million people across the globe, with over 330,000 cases in the United States. To help limit the spread in Massachusetts, the Department of Public Health required that all healthcare workers must be screened for symptoms daily -individuals with symptoms may not work. We rapidly created a digital COVID-19 symptom screening tool for a large, academic, integrated healthcare delivery system, Partners HealthCare, in Boston, Massachusetts.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Large employers both in the healthcare and non-healthcare spaces should consider enacting similar tools and processes. Although others have described their initial experience implementing entry screening tools, [18] this is to our knowledge the first and most longitudinal peer-reviewed data on a commercially-available employee COVID-19 screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…Large employers both in the healthcare and non-healthcare spaces should consider enacting similar tools and processes. Although others have described their initial experience implementing entry screening tools, [18] this is to our knowledge the first and most longitudinal peer-reviewed data on a commercially-available employee COVID-19 screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, during the outbreaks of Ebola and Severe Acute Respiratory Syndrome (SARS), mHealth applications exhibited its potential in screening, detecting, and monitoring such global epidemics [ 14 , 22 , 23 ]. Mobile health technologies and applications have been utilized in this current COVID-19 pandemic and other infectious diseases in most HICs as compared to LMICs [ 24 , 25 , 26 ]. Currently, a study in Canada has revealed that mHealth applications have been utilized for screening, diagnosis, and monitoring of COVID-19 cases [ 14 ].…”
Section: Overviewmentioning
confidence: 99%
“…Commercially available electronic patient-reported outcome (ePRO) platforms were examined to determine their clinical utility and potential implementation during the COVID-19 pandemic. Figure 4 shows an example of the ePRO platform for COVID-19 self-reports [19]. Twelve systems were analyzed.…”
Section: Approach To Identify Suitable Mhealth Technologiesmentioning
confidence: 99%
“…Screenshot of the platform currently utilized by MGB to collect self-reports of COVID-19 symptoms. Image reproduced with permission from Ref [19]…”
mentioning
confidence: 99%